2019
DOI: 10.1007/s00439-019-02005-9
|View full text |Cite
|
Sign up to set email alerts
|

A frameshift insertion in SGK3 leads to recessive hairlessness in Scottish Deerhounds: a candidate gene for human alopecia conditions

Abstract: Hairlessness is a breed-specific feature selected for in some dog breeds but a rare abnormality in some others such as Scottish Deerhounds (SD). In SDs, the affected puppies are born with sparse hair but lose it within the first 2 months leaving the dogs completely hairless. The previous studies have implicated variants in FOXI3 and SGK3 in hairlessness; however, the known variants do not explain hairlessness in all breeds such as SDs. We investigated the genetic c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 25 publications
0
10
0
Order By: Relevance
“…This SGK3 variant leads to a frameshift in the coding sequence and was predicted by Hytonen and Lohi (Hytönen and Lohi 2019) to lead to nonsense mediated decay. The lack of health issues in hairless Scottish Deerhounds, as opposed to observations in loss-of-function mouse models, suggests that perhaps SGK3 is still expressed in hairless dogs.…”
Section: Gene Expressionmentioning
confidence: 81%
See 3 more Smart Citations
“…This SGK3 variant leads to a frameshift in the coding sequence and was predicted by Hytonen and Lohi (Hytönen and Lohi 2019) to lead to nonsense mediated decay. The lack of health issues in hairless Scottish Deerhounds, as opposed to observations in loss-of-function mouse models, suggests that perhaps SGK3 is still expressed in hairless dogs.…”
Section: Gene Expressionmentioning
confidence: 81%
“…The resulting sequence was compared to a recent catalog of 91 million single nucleotide polymorphisms (SNPs) and insertion/deletions (indels) identified from 144 modern breeds, together with a set of wild canids and village dogs (Plassais et al 2019). Our analysis identified the same single, high-impact variant within the coding sequence of the serum/glucocorticoid regulated kinase family member 3 (SGK3) gene as highlighted by Hytonen and Lohi (Hytönen and Lohi 2019). We have previously shown that a distinct mutation in the same gene was responsible for hairlessness in the unrelated American Hairless Terrier breed (AHT) (Parker et al 2017b).…”
mentioning
confidence: 79%
See 2 more Smart Citations
“…Variants in HR in other species are relatively rare, but causal variants of hairless are known in sheep [17], atrichia with papular lesions is also identified in macaques [16], and, in dolphins, evolutionary loss has led to HR as a pseudogene, leading to hypotrichosis in this mammal [20]. Various other genes cause the hairless phenotypes, such as, KRT71 in the sphynx breed [9], and FOXI3 [19] and SGK3 [59,60] in dogs.…”
Section: Discussionmentioning
confidence: 99%